Egress Safety Criteria for Nursing Hospitals - Seung-Ho Choi; Khaliunaa Darkhanbat; Inwook Heo; Hoseong Jeong; Kang Su Kim (Buildings, 2022)
Nursing hospitals have a high probability of casualties during a fire disaster because they have many patients with impaired mobility. In this study, fire and egress simulations were conducted to evaluate the egress safety of a typical nursing hospital. The available safe egress time (ASET) of the prototype nursing hospital was calculated using Fire Dynamics Simulator, and the required safe egress time (RSET) was estimated by Pathfinder, reflecting characteristics of the occupants. The egress safety of the nursing hospital was then evaluated by comparing the ASET and RSET, considering the number of egress guides and delay time. According to the simulation results, the RSET increased as the egress delay time increased and the number of egress guides decreased. In addition, it is estimated that at least 20 workers (egress guides) should be on duty in the prototype nursing hospital, even during shiftwork and night duty. Based on the simulation results, egress safety criteria have been proposed in terms of normalized numbers of egress guides and egress delay time. The proposed criteria can be very easily applied to evaluate the egress safety of a typical nursing hospital in operation.